OUTCOME OF TRAUMATIC BRAIN INJURY IN CHILDREN BY USING ROTTERDAM SCORE ON COMPUTED TOMOGRAPHY - Haque, Anwarul; Dhanani, Zehra; Ali, Amin; Salam, Basit; Abbas, Qalab; Javed, Gohar; Jurair, Humaira - (Journal of Ayub Medical College Abbottabad, 2017)
Background: The Rotterdam Score (RS) on CT head is a new evolving clinical tool as a predictor of mortality in Traumatic Brain Injury (TBI). The objective of this study is to assess the outcome of children with TBI admitted in paediatric intensive care unit (PICU) of a tertiary-care, university hospital by using RS. Methods: This was a prospective observational study conducted on children (age: 1mo -16yr) with TBI admitted in PICU of Aga Khan University Hospital from 2013 to 2016. RS on CT was calculated by a radiologist. All patients were managed according to according to Paediatric Brain Trauma Foundation Guidelines 2012.Demographic data, clinical variables and outcomes were recorded. Logistic regression analysis was applied to assess the association between outcome and R. Results: Ninety-two cases were enrolled during four years. The median age was 77 months (3 months to 16 years) and 73 (79%) were male. The main cause of injury was RTA (60.9%) followed by fall (39.1%). Sixty-two patients (67%) had a post-resuscitation GCS of 8 or less. 54% (51) patients were managed conservatively. The RS of 1, 2, 3, 4 and 5 were present in 19, 36,19,15 and 3 patients. The mean RS was 2.4. The higher mortality rate was observed in high RS. The RS was significantly associated with mortality (OR 1.75, 95% CI 1.03-2.95; p<0.04). Conclusion: Rotterdam Score on CT head can be used to predict mortality in paediatric patients with TBI. Keywords: Children; TBI; Rotterdam score; CT scan; Mortality